Breathing Another’s Burden: An Observational Study on the Awareness and Correlates of Exposure to Secondhand Smoke among Young Adults in Thiruvalla - Joseph S. Mathew; Midhun Pradeep; Shaliet Rose Sebastian (Dentistry and Medical Research)
Background: While not directly inhaling tobacco smoke, non-smokers exposed to second-hand smoke (SHS) are not spared of its harmful effects. Individuals who live with smokers or spend significant time in smoke-filled environments are at a higher risk of experiencing negative health effects from SHS compared to occasional exposure. Objective: To assess the awareness and correlates of exposure to second hand tobacco smoke among young adults in Thiruvalla, Kerala. Methodology: An observational study was conducted among young adults aged between 18 and 30 years in Pathanamthitta district from July to December 2023. The data was analyzed using the IBM statistical package for social sciences version 20. The results have been presented as tables and charts showing percentages. Chi-square test and odds ratio were used for analyzing the association between the study variables and SHS knowledge among the study participants. Results: Out of the 300 study participants, 258 had a good knowledge regarding secondhand smoke. Majority of study participants reported that they were exposed to second hand smoke in public places (90%). Educational status, Smoking status and place of exposure to SHS were found to be associated with SHS knowledge among the study participants in the present study. Conclusion: Passive smoking remains a significant threat to the health of non-smokers. Addressing the gaps in knowledge about the dangers of SHS is crucial for effective public health interventions.